Assessment of presence and grade of activity in ileal Crohn’s disease - Sarıtaş Yüksel, Elif; İpek, Serkan; Topal, Firdevs; Koç, Gonca; Akpınar, Zehra; Slaughter, James C.; Oyar, Orhan; Ünsal, Belkıs (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To assess the sensitivity of magnetic resonance enterography (MRE) in the diagnosis of Crohn’s disease (CD) activity and correlation between endoscopic and MRE scores in predicting the activity grade. Materials and Methods: Twenty-five ileal CD patients with clinical and biochemical evidence of activation underwent ileocolonoscopy and MRE within 7 days of their application. Simplified endoscopic scoring of CD (SES-CD) and MRE scores was done and compared with each other and other parameters of activation (CRP, leukocyte count, platelet count). Results: The sensitivity of MRE scoring was found to be 92%; however, the statistical correlation with SES-CD was not significant (p=0.83) for the grading of the activity. Conclusion: MRE scoring is sensitive enough to use in CD activity evaluation; however, it can not be used alone, and it is rather a complementary technique to endoscopy and is especially valuable for patients with extraluminal disease.